Long noncoding RNA H19 act as a competing endogenous RNA of Let‐7g to facilitate IEC‐6 cell migration and proliferation via regulating EGF. Issue 4 (23rd November 2020) - Li, Cuijie; Li, Ye; Zhuang, Mengmeng; Zhu, Bo; Zhang, Wenwen; Yan, Hao; Zhang, Pan; Li, Dan; Yang, Juan; Sun, Yuan; Cui, Qingwei; Chen, Haijun; et al.
Abstract: Intestinal mucosal injury is one of the most significant complications of burns. In our previous study, it was found that autophagy could alleviate burn‐induced intestinal injury, but the underlying mechanisms are still unclear. Irregular expression of long noncoding RNAs (lncRNAs) is present in many diseases, including burns. However, the relationship between lncRNAs and intestinal mucosal injury requires further elucidation. In this study, we established a burn mice model and detected the expression level of autophagy‐related proteins. Then, H19 content after autophagy intervention was tested in vitro and in vivo. The interaction of H19 with Let‐7g and that of Let‐7g with epidermal growth factor (EGF) were verified by dual‐luciferase reporter assays. We found that the expression of the autophagy‐associated proteins LC3‐II and Beclin‐1 was raised in the intestinal tract of the burn mice model. Similarly, the transfection of H19 raised autophagy levels. H19 was elevated after autophagy intervention in vitro and in vivo. H19 overexpression was able to promote IEC‐6 cell migration and proliferation. Let‐7g was suppressed by the overexpression of H19 and the combination of Let‐7g mimic was able to abolish the physiological effect of H19. Moreover, the suppression of Let‐7g increased the expression of EGF protein, which heightened IEC‐6 cell migration and proliferation. Besides this, dual‐luciferase assays revealed that Let‐7g was a direct target of H19 as well as the EGF gene. Taken together, autophagy‐mediated H19 increases in mouse intestinal tract after severe burn and functions as a sponge to Let‐7g to regulate EGF, which suggests that H19 serves as a potential therapeutic target and biomarker for intestinal mucosal injury after burns. Abstract : Autophagy‐mediated H19 increases in the mouse intestinal tract after severe burn and functions as a sponge to Let‐7g to regulate epidermal growth factor (EGF), which suggests that H19 serves as a potential therapeutic target and biomarker for intestinal mucosal injury after burns.